Adaptations in the transformation of cassava (Manihot esculenta Crantz; Euphorbiaceae) for consumption in the dietary management of diabetes: the case of Palikur, or Parikwene People, from French Guiana - Rapinski, Michael; Cuerrier, Alain; Davy, Damien (Frontiers in Nutrition, 2023)
Introduction In the French overseas department of French Guiana, in South America, nutrition therapy for the management of diabetes is based on French guidelines. However, this region is demographically diverse and includes several populations of Indigenous Peoples, Parikwene among others, also called Palikur. Due to socio-economical, cultural, and geographical differences, along with distinctions in the local food system, dietary recommendations, which many consider in the context of post-colonial power dynamics, are not well suited to local populations. In the absence of suitable recommendations, it is hypothesized that local populations will adapt their dietary practices considering diabetes as an emerging health problem. Methods Seventy-five interviews were conducted with community members and Elders, as well as healthcare professionals and administrators providing services to the Parikwene population of Macouria and Saint-Georges de l’Oyapock communes. Data regarding the representation of cassava (Manihot esculenta Crantz) consumption and diabetes were collected via semi-structured interviews and participant observation (i.e., observation and participation in community activities), namely via participating in activities related to the transformation of cassava tubers at swidden and fallow fields. Results and Discussion Parikwene have adapted the transformation of cassava tubers for their consumption in the management of diabetes.The importance of cassava tubers as a staple and core food to the Parikwene food system was established by identifying it as a cultural keystone species. Narratives illustrated conflicting perceptions regarding the implication of cassava consumption in the development of diabetes. Adaptations to the operational sequence involved in the transformation of cassava tubers led to the production of distinct cassava roasted semolina (i.e., couac), based on organoleptic properties (i.e., sweet, and acidic couac). Preferences for the consumption of acidic couac were grounded in the Parikwene knowledge system, as well as attention to diabetes related symptoms and glucometer readings. Conclusion These results provide important insights related to knowledge, attitudes, and practices in developing locally and culturally adapted approaches to providing dietary recommendations in the treatment of diabetes.